Pengaruh Exterior, General Interior, Store Layout Dan Interior Display Terhadap Minat Beli Konsumen Pada Toko Agung Jaya Elektronik Di Tenggarong - Luthman, Awang Yacoube (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2015)
The purpose of this research is to know and examine the magnitude of the influence of exterior factors, general interior, store layout and interior display of consumer buying interest in Toko Agung Jaya Elektronik in Tenggarong. This study uses quantitative data obtained from questionnaire data. The number of research samples are 48 people with the method of taking by random sampling. The analytical tool used multiple linear regression analysis with hypothesis test using F and t test.From anova test or F test, F arithmetic is 67,219, while the value of F table obtained value of 2.56 this means that (Fcount 67,219> Ftabel 2,56) so it can be said variable exterior, general interior, store layout, and interior Display jointly able to show significant influence on consumer buying interest in Toko Agung Jaya Elektronik in Tenggarong. This is reinforced by the result of the number R is 0.929. It is that the correlation between exterior variables, general interior, store layout, and interior display to consumer buying interest is very strong relation. The adjusted R square is 0.862. This means that 86.2% consumer buying interest can be explained or influenced by exterior, general interior, store layout and interior display variables, while the remaining 13.8% of buying interest is influenced by other causes. So the first hypothesis is accepted.Based on the correlation table shows that the general interior variables have the most dominant influence on buying interest in Toko Agung Jaya Elektronik in Tenggarong which is 0.635 or 63.5% then followed by store layout variables of 0.489 or 48.9%, exterior variables of 0.459 or 45.9% and interior display variables of 0.270 or 27%. From the description, it can be concluded that the second hypothesis is accepted. Keywords : Exterior, General Interior, Store Layout And  Interior Display